Effectiveness of a specialist palliative home care nurse–patient consultation followed by an interprofessional telephone case conference compared with usual care among patients with non-oncological palliative care needs: protocol for the multicentre KOPAL cluster-randomised controlled trial. Issue 7 (25th July 2022) - Marx, Gabriella; Mallon, Tina; Pohontsch, Nadine Janis; Schade, Franziska; Dams, Judith; Zimansky, Manuel; Asendorf, Thomas; Böttcher, Silke; Mueller, Christiane A; Freitag, Michael; Hummers, Eva; van den Bussche, Hendrik; et al.
Abstract : Introduction: Progressive chronic, non-malignant diseases (CNMD) like congestive heart failure (CHF), chronic obstructive pulmonary disease (COPD) and dementia are of growing relevance in primary care. Most of these patients suffer from severe symptoms, reduced quality of life and increased numbers of hospitalisations. Outpatient palliative care can help to reduce hospitalisation rate by up to 50%. Due to the complex medical conditions and prognostic uncertainty of the course of CNMD, early interprofessional care planning among general practitioners who provide general palliative care and specialist palliative home care (SPHC) teams seems mandatory. The KOPAL study (a concept for strenghtening interprofessional collaboration for patients with palliative care needs) will test the effectiveness of a SPHC nurse–patient consultation followed by an interprofessional telephone case conference. Methods and analysis: Multicentre two-arm cluster randomised controlled trial KOPAL with usual care as control arm. The study is located in Northern Germany and aims to recruit 616 patients in 56 GP practices (because of pandemic reasons reduced to 191 participants). Randomisation will take place on GP practice level immediately after inclusion (intervention group/control group). Allocation concealment is carried out on confirmation of participation. Patients diagnosed with CHF (New York Heart Association (NYHA) classification 3–4), COPD (Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage classification 3–4, group D) or dementia GDS stage 4 or above). Primary outcome is a reduced hospital admission within 48 weeks after baseline, secondary outcomes include symptom burden, quality of life and health costs. The primary analysis will follow the intention-to-treat principle. Intervention will be evaluated after the observation period using qualitative methods. Ethics and dissemination: The responsible ethics committees of the cooperating centres approved the study. All steps of data collection, quality assurance and data analysis will continuously be monitored. The concept of KOPAL could serve as a blueprint for other regions and meet the challenges of geographical equity in end-of-life care. Trial registration number: DRKS00017795; German Clinical Trials Register.